Three new species of Ceraclea Stephens 1829 (Trichoptera: Leptoceridae) from Southeast Asia - Laudee, Pongsak; Seetapan, Kriengkrai; Malicky, Hans (Zootaxa, 2017)
Three new species of Ceraclea (Leptoceridae) from Southeast Asia are described and illustrated: Ceraclea (Athripsodina) trisdikooni n. sp. from Myanmar, C. (A.) thongnooi n. sp. from Thailand and Myanmar and C. (A.) thongpongi n. sp. from Laos. Ceraclea trisdikooni n. sp. is distinguished from other species by its inferior appendages recurved ventrad nearly 180° apically. The apex of the basal segment of each inferior appendage is more pointed. In ventral view, each inferior appendage of the new species has an obvious basoventral lobe with numerous long setae. Ceraclea thongnooi n. sp. is distinguished from those by inferior appendages that are each shaped like a seahorse head both in lateral view and ventral view. Ceraclea thongpongi n. sp. is distinguished from other species by the rectangular preanal appendages. In dorsal view, the apical end of segment X is oval and notched apically; in ventral view, the subapicodorsal lobe of each inferior appendage is rounded and straight.